2023
DOI: 10.1097/mot.0000000000001123
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the limits of treatment for hepatocellular carcinoma

Michelle Jones-Pauley,
David W. Victor,
Sudha Kodali

Abstract: Purpose of review We review existing and newer strategies for treatment and surveillance of hepatocellular carcinoma (HCC) both pre and postliver transplantation. Summary HCC is rising in incidence and patients are often diagnosed at later stages. Consequently, there is a need for treatment strategies which include collaboration of multiple specialties. Combinations of locoregional, systemic, and surgical therapies are yielding better postliver transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Both studies reported that the combination of ATE + BEV and radiotherapy showed tolerable and manageable toxicity. Jones-Pauely et al suggested that combination of systemic and locoregional therapy might provide patients with large tumor burden opportunity from effective tumor control to downstaging [25]. However, this alone cannot explain all the success which occurred in the high-risk group because more than half of the highrisk group in this study had extrahepatic metastases that were not covered by radiation therapy.…”
Section: Discussionmentioning
confidence: 70%
“…Both studies reported that the combination of ATE + BEV and radiotherapy showed tolerable and manageable toxicity. Jones-Pauely et al suggested that combination of systemic and locoregional therapy might provide patients with large tumor burden opportunity from effective tumor control to downstaging [25]. However, this alone cannot explain all the success which occurred in the high-risk group because more than half of the highrisk group in this study had extrahepatic metastases that were not covered by radiation therapy.…”
Section: Discussionmentioning
confidence: 70%